Measurement of Muscle Flexibility and Speed In Sprinters Following Stretching - Applicability of a New Range of Motion Instrument (International Journal of Physiotherapy, 2024)
Background: The study aimed to compare static stretching (SS) and proprioceptive neuromuscular facilitation stretching (PNFS) on tight hamstrings in sprinters and use a new range of motion instrument instead of a traditional goniometer to document knee extension deficit.Methods: The study involved 80 male subjects(age of 18.75±1.94 years), randomized into SS and PNFS groups. Data on age, height, weight, BMI, hamstring flexibility, and speed parameters were recorded at the beginning and 12 weeks. The material includes an examination couch, a Pheezee device for Knee ROM, a Mobile device for Pheezee data display, and a synthetic track for a 30-meter sprint.Results: Ranges and averages of all parameters calculated, and the significance of the differences in flexibility and speed within and between groups tested. SS group knee extension deficit (KED) 27.1±3.84 decreased to 11.67±5.3.49 and in the PNF group, 27.3 ±4.41 to 10.3±3.33. Thirty-meter sprint test performance in the SS group improved from 5.75±0.47 to 4.77± 0.45, and in the PNF group, 5.77±0.45 to 3.99± 0.26 within group results of both speed and flexibility in both groups was significant (P=< .001). Group KED and speed results differences were clinically significant in pre and post-intervention, but statistically, the results were similar.Conclusion: Hamstring flexibility impacts knee extension deficit and sprinting speed. Both stretching types showed an impact on knee extension deficit and speed. PNF stretching enhanced speed-related functional outcomes better than Static stretch. The study supports the applicability of the Pheezee instrument and its ability to record Knee extension deficits in field and clinical research.